COVID-19 Associated With Life-Threatening Apnea in an Infant Born Preterm: A Case Report - Loron, Gauthier; Tromeur, Thibault; Venot, Perrine; Beck, Jonathan; Andreoletti, Laurent; Mauran, Pierre; Bednarek, Nathalie (Frontiers in Pediatrics, 2020)
A pandemic linked to the new coronavirus strain (SARS-CoV-2) has been raging for several months. Pediatric populations are less impacted than adults, and critical respiratory diseases seem rare (1,2). We report the case of an infant, who presented with life-threatening apneas at home requiring basic life support. SARS-CoV-2 was subsequently identified in the patient’s nasopharyngeal aspirate. He did not present with bronchiolitis or hypoxic failure as described in severe forms of COVID -19. The outcome was favorable in a few hours. The occurrence of apneas is not uncommon during viral respiratory infections in early infancy; however, there are very few descriptions related to a documented SARS-CoV-2 respiratory tract infection. In light of this clinical case, it seems necessary to quickly bring up a potential COVID-19 contamination in infants admitted for life-threatening apnea, in order to properly report and isolate these patients to avoid further nosocomial dissemination of SARS-CoV-2.